Pengaruh Financial Performance terhadap Zakat Perusahaan dengan ROA Sebagai Variabel Intervening pada Bank Umum Syariah di Indonesia - Naila Shafia Hamid Alfani; Mochamad Edman Syarief; Rani Putri Kusuma Dewi (Journal of Applied Islamic Economics and Finance, 2022)
In 2016-2020 there was a phenomenon where ROA, the variables that affect ROA, and ZAKAT are fluctuated which made the authors interested in doing research again. Based on this phenomenon, this study aims to determine how the variables of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and Financing to Deposite Ratio (FDR) influence the Return On Assets (ROA) and their effect on the Zakat Expenditure. The population used is Islamic Banks registered with the Financial Services Authority using purposive sampling. The software used in data processing is WarpPLS 7.0 using descriptive quantitative research methods. This study will provide an overview of how the influence of Conventional Financial Performance on Zakat Expenditure with profitability as the intervening variable. The results showed that ROA had a significant effect on ZAKAT and could mediate between CAR and NPF variables on ZAKAT. While the FDR variable has no effect on ROA and ZAKAT.